Microbial quality of artisanal yoghurt and Dèguè products collected in schools of Cotonou and Abomey-Calavi (Benin) - SINA, HAZIZ; Mousse, Wassiyath; Tohoyessou, Majoie Géroxie; BADE, Farid; AHOUISSOU, Oswald R.; Adjanoho, Adolphe; BABA-MOUSSA, LAMINE SAÏD; BOTON, Chédrac A. (My University, 2020)
The main aim of this study is to evaluate the microbiological quality of yoghurt and two types of dèguè (couscous and millet) sold in Cotonou and Abomey-Calavi. Samples of dairy products were collected in 15 schools of Abomey-Calavi and Cotonou from vendors located inside the schools. In this study, 180 samples (60 yoghurt, 60-dèguè millet and 60-dèguè couscous) were analysed. The microbial quality of collected samples was investigated using conventional methods for lactic acid bacteria, staphylococci, faecal and total coliforms and thermo-tolerant Gram-negative bacilli bacteria. The results of the microbiological analyses of the collected samples revealed a contamination of all the samples of yoghurt, dèguè millet and dèguè couscous. The microorganisms load varies according to not only the sampling sites, the sampling period but with the type of microorganisms. The presence of potentially pathogenic bacteria particularly the total coliforms (38%), faecal coliforms (21%), and thermo-tolerant Gram-negative bacilli bacteria (20%) and staphylococci (21%) were observed. In addition, it should be noted that the different samples of yoghurt, dèguè millet and dèguè couscous taken in the morning have a high microbial load compared to that of the evening with regard to faecal coliforms for the two sites. Dairy products sold to school children in Cotonou and Abomey-Calavi are potentially sources of food poisoning.
Keywords: Yoghurt; dèguè; microbiological quality; schools; South Benin.